Mechanical, degradation and cytocompatibility properties of magnesium coated phosphate glass fibre reinforced polycaprolactone composites - Liu, Xiaoling; Hasan, Muhammad Sami; Grant, David M.; Harper, Lee Thomas; Parsons, Andrew J.; Palmer, Graham; Rudd, Chris D.; Ahmed, Ifty (SAGE, 2014)
Retention of mechanical properties of phosphate glass fibre reinforced degradable polyesters such as polycaprolactone and polylactic acid in aqueous media has been shown to be strongly influenced by the integrity of the fibre/polymer interface. A previous study utilising ‘single fibre’ fragmentation tests found that coating with magnesium improved the fibre and matrix interfacial shear strength. Therefore, the aim of this study was to investigate the effects of a magnesium coating on the manufacture and characterisation of a random chopped fibre reinforced polycaprolactone composite. Short chopped strand non-woven phosphate glass fibre mats were sputter coated with degradable magnesium to manufacture phosphate glass fibre/polycaprolactone composites. The degradation behaviour (water uptake, mass loss and pH change of the media) of these polycaprolactone composites as well as of pure polycaprolactone was investigated in phosphate buffered saline. The Mg coated fibre reinforced composites revealed less water uptake and mass loss during degradation compared to the non-coated composites. The cations released were also explored and a lower ion release profile for all three cations investigated (namely Na+, Mg2+ and Ca2+) was seen for the Mg coated composite samples. An increase of 17% in tensile strength and 47% in tensile modulus was obtained for the Mg coated composite samples. Both flexural and tensile properties were investigated and a higher retention of mechanical properties was obtained for the Mg coated fibre reinforced composite samples up to 10 days immersion in PBS. Cytocompatibility study showed both composite samples (coated and non-coated) had good cytocompatibility with human osteosarcoma cell line.